Perspective: Minimally clinically important “symptomatic” benefit associated with disease modification resulting from anti‐amyloid immunotherapy - John Alam; Marwan N. Sabbagh (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Despite some skepticism regarding the amyloid hypothesis, there is growing evidence that clearing amyloid by targeting specific species of amyloid (plaque, oligomers, fibrils, and protofibrils) for removal has therapeutic benefits. Specifically, there is growing evidence that, in mild cognitive impairment and mild dementia due to Alzheimer's disease (AD), robust and aggressive removal of amyloid can slow cognitive decline as measured by global instruments, composite measures, and cognitive testing. Furthermore, clinical efficacy signals coupled with clear biomarker changes provide the first evidence of disease modification. This effect seems to be in addition to symptomatic treatments and opens speculation that the effect of anti‐amyloid monoclonal antibodies might be clinically meaningful through symptomatic amelioration that is a result of disease modification. Highlights Clearance of brain amyloid plaques may lead to a clinical benefit in patients with early AD. Aggregated Aβ may play a role in both disease expression and progression. Anti‐amyloid monoclonal antibodies might be clinically meaningful through symptomatic amelioration resulting from disease modification.